Aesthetic Discipline and Creative Development: A Calligraphy-Based Intervention in Teacher Education - Lia Mareza; Agung Nugroho; Masanori Fukui (Jurnal Tarbiyatuna, 2026)
Preparing teachers who are creative, reflective, and ethically grounded remains a major challenge in teacher education. This study examined the effectiveness of an Islamic calligraphy-based learning program in fostering creativity and professional character among pre-service elementary teachers. A quasi-experimental pretest-posttest control group design was employed with 60 participants, comprising 30 students in the experimental group and 30 in the control group. The experimental group participated in an eight-session Islamic calligraphy program, whereas the control group received conventional visual arts instruction. Creativity was assessed across four dimensions fluency, flexibility, originality, and elaboration while professional character was measured through discipline, perseverance, responsibility, reflective awareness, and aesthetic sensitivity. Data were analyzed using paired-sample and independent-sample t-tests, effect size analysis, and Pearson correlation analysis. The findings showed that participants in the experimental group demonstrated significantly greater improvements in creativity and professional character than those in the control group. The largest gains were observed in originality, elaboration, discipline, and perseverance. Creativity was also positively associated with professional character development. These findings suggest that Islamic calligraphy can serve as an effective aesthetic pedagogical approach to fostering creativity and professional character in teacher education.